STUDENTS’ MISCONCEPTIONS AND THE CAUSES ON STRAIGHT MOTION MATERILAS USING SIX-TIER MULTIPLE CHOICE - Kusuma, Witya; Sundari, Putri Dwi; Hufri, Hufri; Hidayati, Hidayati (Universitas Negeri Padang, 2024)
In physics studies, students experience misconceptions in physics learning, no exception to straight motion materials. These misconceptions can be identified using diagnostic tests, but diagnostic tests are not yet available in schools. To solve this problem, a test instrument is needed that can identify student misconceptions on direct motion material. The study aims to analyze the misconceptions of the students and their causes in straight motion. The instrument used in identifying misconception and its causes is the Six-Tier Multiple Choice which consists of 17 elements of six-level double choice on straight motion material. The type of research used is descriptive research with a quantitative approach.The population in this study is a student of class XI MIPA State High School in Bungo district. The sample in this research is five schools in Bongo district with the number of respondents is 127 pupils. The highest misconception was found in High School E, 35.29% and the lowest was found at High School A, 15.03%. The main cause of misconceptions in students was from the personal thinking of students 76.57% of the total of 22 students.